Generating optimal reference kinematic configurations for hyper-redundant parallel robots. (October 2015) - Chibani, Abdelhakim; Mahfoudi, Chawki; Chettibi, Taha; Merzouki, Rochdi; Zaatri, Abdelouhab
In this article, we propose an optimization process able to generate optimal kinematic configuration for spatial hyper-redundant manipulators with multiple rigid parallel modules. The proposed method uses a deterministic optimization scheme that evaluates the score of trial kinematic configurations while accounting for various geometric constraints. This versatile method is based on a simultaneous search for both the best curve capturing the overall kinematic robot posture and the platform distribution along this curve. This process is carried out using the powerful sequential quadratic programming technique. Numerical results are presented to illustrate the efficiency of the proposed approach. Finally, this model was validated by real measurements obtained with the continuum bionic handling arm of a mobile robot called Robotino-XT.